Tinjauan Prosedur Pengisian Notam di UPBU pada PIA Wilayah Jakarta - Metha Yurike Cartika; Dhian Supardam; Novita Ayu Permatasari (LPPM Politeknik Pratama, 2025)
This study examines the NOTAM submission procedures at Airport Operator Units (UPBU) within the Aeronautical Information Service (PIA) in the Jakarta region. The background of the problem is the discrepancy between current procedures and the CASR 139 regulation, where errors in NOTAM submission such as typos, incorrect dates, or NOTAM content can pose a significant threat to flight safety. This research aims to analyze the impact of these errors and identify the contributing factors. Using a qualitative methodology, the study delves into in-depth information from the personnel involved to understand their experiences and challenges. The findings reveal that UPBU reporting officers do not adhere to the CASR 139 document because they have not received specific training or briefings on NOTAMs before assuming their duties. This lack of understanding leads to inaccurate NOTAM data submissions, deviating from the standards outlined in the CASR 139 document. As a solution, this study proposes the implementation of a specific training program for NOTAM reporting personnel to improve their understanding and competence, ensuring that NOTAM procedures are carried out according to the proper standards to maintain flight safety.